The Impact of Information and Information System on Managerial Decision Making: The Case of Telecommunication Sector in Jordan - Al Haraisa, Yazan Emnawer Qteesh (2011)
The study investigates relationship between management information systems, information technology systems and managerial decision making in the telecommunication sector in Jordan. A survey questionnaire was sent to IS mangers, IS directors, IS professionals and staff in private company based in Jordan. The findings of the study reveal that there is a positive relationship between management information systems and managerial decision making. The study also found that there is a positive relationship between information technology systems and managerial decision making. On other hand in this study there are two types of statistical analyses that were carried out on the data obtained from the respondent. First, descriptive analysis was used to analyze the background of the respondent and the private companies; second, correlation analysis was used to analyze the relationship between management information systems, Information Technology systems and managerial decision making. And the Data were collected through questionnaires from the respondents of telecommunication sector in Jordan and the data were collected from the respondent by using structured questionnaires. A total 150 questionnaires for the study were distributed to the respondents by e-mail and also by hand.Out of 150 the questionnaires distributed, 135 were returned on 8 January 2010. The data of 150 participants are potentially available for analysis. Analyses were conducted using descriptive statistics and correlation analysis.